2009
DOI: 10.7326/0003-4819-151-10-200911170-00009
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Breast Cancer: An Update for the U.S. Preventive Services Task Force

Abstract: Background This systematic review is an update of evidence since the 2002 U.S. Preventive Services Task Force (USPSTF) recommendation on breast cancer screening. Purpose To determine the effectiveness of mammography screening in decreasing breast cancer mortality among average-risk women age 40 to 49 and 70 and older; the effectiveness of clinical breast examination (CBE) and breast self examination (BSE); and harms of screening. Data Sources Cochrane Controlled Trials Registry and Database of Systematic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
772
2
42

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,068 publications
(840 citation statements)
references
References 55 publications
7
772
2
42
Order By: Relevance
“…Although screening tests including mammography, colonoscopy, and sigmoidoscopy have established populationlevel health benefits, [9][10][11][12] these tests also carry risks; as such, there is a desire to identify individuals who will derive the greatest benefit and least harm. Genetic testing for cancer susceptibility may have utility for risk stratification, thereby allowing for a more focused application of screening tests to those at greatest disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although screening tests including mammography, colonoscopy, and sigmoidoscopy have established populationlevel health benefits, [9][10][11][12] these tests also carry risks; as such, there is a desire to identify individuals who will derive the greatest benefit and least harm. Genetic testing for cancer susceptibility may have utility for risk stratification, thereby allowing for a more focused application of screening tests to those at greatest disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although the UK Age Trial showed a non-significant 17% reduction in breast cancer mortality, 9 a statistically significant breast cancer mortality reduction of 15% to 18% associated with screening for women aged 39 to 49 or 40 to 49 at entry was demonstrated by several meta-analyses of randomised controlled trials. [10][11][12][13] In addition, a recent Swedish observational study that compared breast cancer mortality rates between women aged 40 and 49 who were invited to screening and women who were not invited to screening demonstrated a 26% statistically significant breast cancer mortality reduction. 14 Younger women may benefit less from mammography screening because of factors associated with younger age, including a lower breast cancer incidence 1 and a lower test sensitivity of mammography due to higher breast density and, possibly, faster growing tumours.…”
mentioning
confidence: 99%
“…1,2 Evidence behind this decision included a meta-analysis that revealed that while mammography does reduce mortality in this age group, there are more false positives than in older women and the number needed to treat is higher due to lower incidence. 3 Therefore, screening mammography in this younger age group could lead to costly and anxiety-provoking workups, which are associated with their own health risks, as well as to potential over-diagnosis. 4 The new guidelines led to resistance among the media, patients, providers, and medical organizations.…”
mentioning
confidence: 99%